Structures Congress 2013 2013
DOI: 10.1061/9780784412848.175
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Modeling Uncertainties Based on the Blind Prediction Contest Submissions

Abstract: Modeling uncertainty can have a significant impact on the assessed risk of earthquake-induced damage and collapse in a building obtained through the performance-based earthquake engineering framework. This paper quantifies the effect of modeling uncertainty on performance-based risk assessments, accounting for differences in software platforms, solution algorithm, element-types, and model parameter calculation or selection, using results of the 7-story reinforced concrete (RC) building blind prediction contest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Collapse modes not modeled herein (e.g., failures in the gravity framing system) would likely occur well before 20% is reached. The impact of modeling uncertainty (Sattar et al 2013, Ibarra and Krawinkler 2005a) is not considered in this study.…”
Section: Building Description and Modelingmentioning
confidence: 99%
“…Collapse modes not modeled herein (e.g., failures in the gravity framing system) would likely occur well before 20% is reached. The impact of modeling uncertainty (Sattar et al 2013, Ibarra and Krawinkler 2005a) is not considered in this study.…”
Section: Building Description and Modelingmentioning
confidence: 99%
“…Therefore, we do not account for aleatory or epistemic uncertainties in material properties, nonlinear component modeling parameters, element stiffness, or damping. Modeling uncertainties can significantly affect the results in some cases (Sattar et al, 2013). Uncertainties in the observed damage and measured response are not considered in this study and only best estimates and available data are used for comparison; omission of these uncertainties are justified as uncertainties in measured responses are difficult to quantify and expected to be relatively small compared to modeling and material uncertainties.…”
Section: Benchmark Comparisonsmentioning
confidence: 99%
“…TN.1992 drift is reached. The impact of modeling uncertainty is not considered in this study, but has been shown that it can influence results in other studies (e.g., Sattar et al (2013) ). Figure 2.…”
Section: Overview Of Perform-3d Modelmentioning
confidence: 99%